2020
DOI: 10.1016/j.ajp.2020.102076
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the anxiety level of Iranian general population during COVID-19 outbreak

Abstract: The inferential statistics suggests that the level of anxiety was higher among women (95 % CI [0.1, 81.36], p < 0.001), people who more followed corona-related news (p < 0.001) and the age group of 21-40 years (p < 0.001). Ultimately, the level of anxiety was significantly higher among people who had at least one family member, relative, or friend who contracted COVID-19 disease (95 % CI [1.2, 35.03], p < 0.001). The health care system should adopt a package of psychosocial interventions to reduce the anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

94
593
20
50

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 646 publications
(757 citation statements)
references
References 13 publications
94
593
20
50
Order By: Relevance
“…Reason of association between female sex and self-medication is not clearly known, but in the context of Covid-19 outbreak, greater anxiety among women as described in Iran and Italy could not be excluded [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Reason of association between female sex and self-medication is not clearly known, but in the context of Covid-19 outbreak, greater anxiety among women as described in Iran and Italy could not be excluded [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang, J. et al (10) An increased prevalence of depression (29.2%) was observed in patients infected with COVID-19 (p 0.016). There was an increase in the prevalence of comorbid depression with anxiety (p 0.086) both in patients infected with COVID-19 (21.1%), and in the general public (22.4%).…”
Section: (6) Ymentioning
confidence: 94%
“…In addition, seven studies addressed the relationship between COVID-19 and MH among women. 10,12,18,20,33,38,49 The elderly Elderly subjects are more susceptible to depressive symptoms, due to losses they experience during their lives and cerebral vascular changes.55 Depression and anxiety in the elderly appear among the most frequent reasons for requesting a psychiatric consultation.56 The elderly population are among the most affected by the COVID-19 pandemic, both in terms of severity and mortality, and are also more likely to suffer psychological impacts during this period.4,57…”
Section: Speci C Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moghanibashi-Mansourieh. found that the level of anxiety in women was signi cantly higher than men in the COVID-19 outbreaks (35) and Lee DT et al reported that the anxiety levels of pregnant women at the peak of the SARS outbreaks in Hong Kong were slightly higher than a comparative pre-SARS group (36).…”
Section: Discussionmentioning
confidence: 99%